Verification of Ge-on-insulator structure for a mid-infrared photonics platform - Kim, SangHyeon; Han, Jae-Hoon; Shim, Jae-Phil; Kim, Hyung-Jun; Choi, Won Jun (OPTICAL SOC AMER, 2018)
We propose a new Ge waveguide platform on Si substrates using F- and Y-based insulator cladding such as CaF2 and Y2O3, which have a small refractive index, broad transparency range, and high thermal conductivity. First, we verified the platform by optical mode simulation, showing that Mid-infrared (MID-IR) light is well confined in the proposed Ge waveguide due to the large differences in the refractive indexes of Ge and the insulators. We also investigated the thermal aspects of the platform in order to quickly dissipate the heat for stable light source integration. It was found that our platform provided better thermal dissipation than conventional SOI platforms due to large thermal conductivity of CaF2 and Y2O3. Furthermore, we provide a fabrication method for a Ge-on-insulator (GOI) platform using wafer bonding and splitting techniques. Finally, the optical transparency of the materials used in the platform were characterized at the MID-IR wavelength range and demonstrate that the platform can cover at wide wavelength range of up to at least 13 mu m. (c) 2018 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
Keywords: WAVE-GUIDES; SILICON PHOTONICS; BROAD-BAND; GERMANIUM; LASER; WAFER; SPECTROSCOPY; FILMS